Theoretical method of determining pier settlement limit value for China's high-speed railway bridges considering complete factors. (15th April 2020) - Chen, Zhaowei; Zhai, Wanming
Highlights: A novel method to determine bridge pier settlement limit value is proposed. Bridge deformations caused by the different factors are investigated and compared. Train vibration caused by multiple factors are comprehensively investigated. Pier settlement limit value for China's high-speed railway bridges is suggested. Abstract: Reasonable pier settlement is an extremely important limit value in the design of high-speed railway bridges, which directly affects the service performance of bridges and the running safety of trains. Comprehensively considering complete factors affecting the determination of pier settlement limit value (PSLV), this paper presents a method to investigate PSLV for simply supported girder bridges in China's high-speed railways. First of all, an investigation on PSLV written in China's current codes is conducted to explain the necessity of this present work. Then based on the train-track-bridge dynamic interaction theory, the methodology for determining PSLV for China's high-speed railway bridges is proposed, in which the complete factors affecting the determination of PSLV are emphatically discussed and summarized. Adopting the established model, the bridge deformations caused by different factors are calculated, and the PSLV for China's high-speed railway bridges is then obtained according to the running safety and ride comfort of high-speed trains. Results show that important factors written in codes, including self-weight, prestress, creep, shrinkage, temperature and rail random irregularity, should be fully considered in determining PSLV due to these factors greatly affect bridge deformations and dynamic behaviors of running trains. According to the running safety and ride comfort of high-speed trains, the PSLV for simply supported girder bridges in China's high-speed railways is suggested to 12.7 mm.